Looking in the mirror: capturing the facets of Wellcome Collection's identity. Issue 1 (January 2020) - Oke, Arike; Zimmermann, Trudy
Abstract : What is now the Wellcome Trust was established in 1936 under the will of pharmacist, entrepreneur, philanthropist and collector Sir Henry Wellcome. It is now a global charitable foundation which aims to improve health for everyone by helping great ideas to thrive. Wellcome Collection is one of the world's major resources for the study of medical history. The collections, in continual development, can challenge the ways in which people think and feel about health by connecting science, medicine, life and art - but how can Wellcome's ambition match reality without also including its own history? Only in recent years has Wellcome begun to think systematically about capturing its own institutional memory. In efforts to collect Wellcome's own archival heritage, the institution faces the peculiarities of its own character: it is neither solely a research institution, nor a charity, nor a corporate institution. Wellcome is committed to open access to research, but without an accessible history, is it closed? This article explores Wellcome's plurality of identities. It examines "collecting ourselves" against a backdrop in which notions of "us" as the collector of "others" are embedded. It explores the anxieties and opportunities generated by such collecting, and how this collecting can be a sustained part of what Wellcome does.